Transporters in Drug Development: 2018 ITC Recommendations for Transporters of Emerging Clinical Importance. Issue 5 (8th August 2018) - Zamek‐Gliszczynski, Maciej J.; Taub, Mitchell E.; Chothe, Paresh P.; Chu, Xiaoyan; Giacomini, Kathleen M.; Kim, Richard B.; Ray, Adrian S.; Stocker, Sophie L.; Unadkat, Jashvant D.; Wittwer, Matthias B.; Xia, Cindy; Yee, Sook‐Wah; et al.
Abstract : This white paper provides updated International Transporter Consortium (ITC) recommendations on transporters that are important in drug development following the 3 rd ITC workshop. New additions include prospective evaluation of organic cation transporter 1 (OCT1) and retrospective evaluation of organic anion transporting polypeptide (OATP)2B1 because of their important roles in drug absorption, disposition, and effects. For the first time, the ITC underscores the importance of transporters involved in drug‐induced vitamin deficiency (THTR2) and those involved in the disposition of biomarkers of organ function (OAT2 and bile acid transporters).